3D planning in mandibular fractures using CAD/CAM surgical splints — A prospective randomized controlled clinical trial. Issue 4 (April 2020) - Ramanathan, Mrunalini; Panneerselvam, Elavenil; Krishna Kumar Raja, V.B.
Abstract: This randomized controlled trial assessed the role of CAD/CAM splints in achieving anatomic reduction of fractured fragments and ideal occlusion, in comparison with conventional splints. Patients diagnosed with displaced mandibular fracture and post-traumatic malocclusion were allocated to study and control groups by simple randomization. A standardized surgical approach was followed to expose the fractures. Reduction of fractures was carried out using CAD/CAM and conventional splints in the study and control groups, respectively. The parameters assessed were: occlusion, interfragmentary separation, fit of the splint, patient comfort, and surgeon comfort. Mann-Whitney U tests were used to compare the study and control groups. To compare the groups pre- and post-intervention Wilcoxon signed rank tests were used. Chi-square tests were applied for proportion comparisons. The sample consisted of 30 patients. The study group demonstrated superior clinical outcomes with regards to intraoperative reduction of fracture ( p < 0.001; mean – 3.93, SD – 1.43), and to achieving intraoperative occlusion ( p = 0.483) and postoperative occlusion ( p = 0.224). Statistically significant improvements in both patient comfort ( p < 0.001; mean – 0.20, SD – 0.41) and surgeon comfort ( p < 0.001) were found in the study group. In conclusion, CAD/CAM splints improve precision in fracture reduction and restoration of occlusion through a simple fabrication process.